Exploring Nano Simply Open Sets in Nano Topology: Applications and Insights - El Sayed, M. (PT Mattawang Mediatama Solution, 2025)
In recent times, nano set theory has shown broad applications in addressing practical challenges in various domains, including engineering, social sciences, and healthcare sciences. The notion of nano topological spaces, along with associated concepts like nano near open sets, has greatly developed because of its practical usefulness. The idea of nano continuity extends the idea of continuity. Likewise, nano open sets extend the notion of open sets within topological spaces. This paper presents a new class of nano near open sets, termed